SUPRACONDYLAR HUMERAL FRACTURE IN CHILDREN: MANAGEMENT BY PERCUTANEOUS LATERAL-ENTRY PIN FIXATION - ., Shahabuddin; Shahab, Faseeh; Rehman, Khalil ur; Hussain, Khadim (Journal of Postgraduate Medical Institute, 2014)
This case series was conducted at the Department of Orthopaedics and Traumatology,Lady Reading Hospital Peshawar, from January 2007 to June 2008to assess the outcome of two percutaneous lateral-entry pins in the operativemanagement of supracondylar humeral fractures. The study includedmanagement of Type II and III displaced supracondylar humeral fractures accordingto Wilkins's modification of Gartland's classification system in 193patients. The fractures were fixed with two percutaneous lateral-entry pins.Seventy-two children had Type II fracture and One Hundred and Sixty-fivechildren presented with Type III fracture according to Wilkins's modificationof Gartland's classification system. A comparison of perioperative and finalradiographs showed no loss of reduction of any fracture. There was no hyperextension,loss of motion, cubitus varus, iatrogenic nerve palsies and nopatient required additional surgery. Six patients had pin tract infection. Followup rate was 81.5% Results were evaluated by Flynn's Criteria, 93.3% Excellent/good results were obtained. In this case-series, the use of lateral-entry pinswas found to give excellent/very good results. It is an effective treatment optionfor unstable supracondylar fractures of humerus in children. This methodprovides the greatest skeletal stability and prevents neurovascular complicationsin children, as in other techniques, hence giving excellent results.